Surface immobilization of star-shaped poly(ethylene oxide) on poly(dimethylsiloxane) - Park, YS; Kang, YS; Won, J (WILEY-BLACKWELL, 2002)
A thin layer of star-shaped poly(ethylene oxide) (PEO) (starPEO), on the polydimethylsiloxane (PDMS) membrane was prepared by a simple immobilization procedure. Photoreactive molecules were introduced on the surface of the polymeric support to achieve the formation of thin starPEO film from the materials having no functional groups. This novel technique enabled us to immobilize any kind of chemical, especially one that had no functional groups, and readily to control the amount of immobilization. The gas permeation properties of the starPEO-immobilized PDMS membranes were investigated for pure propane and propylene. The permeance of gases were found to decrease in the starPEO-immobilized PDMS membranes, although the ideal separation factors for propylene/propane were increased with the loading amount of silver ions, because of the facilitation action of silver ions in the immobilized PEO unit on the PDMS membranes, as propylene carriers. (C) 2002 John Wiley Sons, Inc.
Keywords: SILICONE ELASTOMER SURFACES; POLY(PROPYLENE OXIDE); POLYMER ELECTROLYTES; COMPLEXES